The actuality and influences of undergraduates’ participation in high impact educational practices in Chinese universities - Ke, Hu; Jianchao, Ni; Xiaojing, Li; Xiting, Zhou (Frontiers in Psychology, 2022)
High Impact Educational Practices (HIPs) are effectively educational practices that have an important impact on student learning and development. This study uses multiple linear regression analysis methods to explore the impact of HIPs on student learning Based on China College Student Survey 2019. It’s found that most Chinese college students do not perform well on HIPs, while the “Double First-Class” university students engage more than other colleges. Participating in HIPs has a significant impact on students’ knowledge, ability and values, especially on the latter two. Universities should increase institutional support and provide students with learning resources and opportunities to participate in HIPs. Meanwhile, it’s also necessary for them to renew the educational pedagogy and pay attention to the all-rounded role of HIPs.